Gossypiboma Causing Mechanical Intestinal Obstruction: A Case Report - Akin Aydogan; Seckin Akkucuk; Ibrahim Yetim; Orhan Veli Ozkan; Murat Karcioglu (Case Reports in Surgery)
Introduction. Gossypiboma (GP) is a term used to express the mass resulting from forgotten cotton sponge in operations. Rarely, a transmural migration may occur into the gastrointestinal lumen without creating any defect by GP. Laparotomy or endoscopic removal may be required, by the way it can be taken out of the body itself by intestinal ways. In this study, we reported a case of mechanical intestinal obstruction causing GP. Case. The fifty-one-year-old female patient admitted to the emergency department with the complaints of mechanical intestinal obstruction and had a history of open cholecystectomy 20 years ago. There were the findings of intestinal obstruction in abdominal plain radiography and computerized tomography. The sponge that obstructed the lumen completely 40 cm proximal to the ileocecal valve was identified in the laparotomy with the diagnosis of brid ileus. The small intestine was closed over double-fold after removal of sponge. Transmural migration of abdominal-remained sponge was thought to be occurred without creating a defect after cholecystectomy. Postoperatively, the patient was discharged without having any problems at 4th day of hospitalization. Conclusion. Although it is a rare situation in routine clinical practice, GP should be considered as a differential diagnosis in the patients who had a diagnosis of mechanical intestinal obstruction, and laparotomy was applied before. As GP may lead to situations which cause mortality, all precautions should be taken to prevent it.